Effect of the number of practicum courses programmed on the scientific attitude of biology education students in South Kalimantan - M. Arsyad; Ayu Rizki Annisa (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
Practical activities are one of the activities that can improve science process skills and influence scientific attitudes. A scientific attitude is important for biology education students to have as pre-service biology teachers. This research aims to analyze differences in scientific attitudes between groups of students with differences in the number of practicum courses that have been programmed and to analyze the effect of the number of practical courses that have been taken on the scientific attitudes of Biology Education students in South Kalimantan Province, Indonesia. The type of this research is quantitative. The research subjects were 245 Biology Education students in South Kalimantan from Lambung Mangkurat University, Antasari Islamic State University Banjarmasin, and PGRI University Kalimantan. Data were collected using a scientific questionnaire.  Analysis of differences in scientific attitudes in each group of students was carried out using the Kruskal-Wallis test and continued with the Mann-Whitney test. Effect analysis was carried out using a linear regression test. The research results show that there are differences between student groups with differences in the number of practical courses that have been programmed. The results of the analysis also show that there is an effect of the number of practicum courses on the scientific attitudes of biology education students in South Kalimantan. The results of this study can be used as a consideration in curriculum development and the provision of infrastructure in the Biology Education Study Program.Abstrak. Kegiatan praktikum merupakan salah satu kegiatan yang dapat meningkatkan keterampilan proses sains dan berpengaruh terhadap sikap ilmiah. Sikap ilmiah penting untuk dimiliki mahasiswa Pendidikan biologi sebagai calon guru biologi. Penelitian ini bertujuan untuk menganalisis perbedaan sikap ilmiah antar kelompok mahasiswa dengan perbedaan pada jumlah mata kuliah berpraktikum yang telah diprogram, dan untuk menganalisis pengaruh jumlah mata kuliah berpraktikum yang telah ditempuh terhadap sikap ilmiah mahasiswa Pendidikan Biologi di Provinsi Kalimantan Selatan, Indonesia. Penelitian ini merupakan penelitian kuantitatif. Subjek penelitian merupakan mahasiswa Pendidikan Biologi di Kalimantan Selatan dari Universitas Lambung Mangkurat, UIN Antasari Banjarmasin, dan Universitas PGRI Kalimantan berjumlah 245 orang. Data dikumpulkan dengan menggunakan angket. Analisis perbedaan sikap ilmiah pada masing-masing kelompok mahasiswa dilakukan dengan menggunakan uji Kruskal-Wallis dan dilanjutkan dengan uji Mann-Whitney. Analisis pengaruh dilakukan dengan uji regresi linear. Hasil penelitian menunjukkan terdapat perbedaan antar kelompok mahasiswa dengan perbedaan pada jumlah mata kuliah berpraktikum yang telah deprogram. Hasil analisis juga menunjukkan adanya pengaruh jumlah mata kuliah berpraktikum terhadap sikap ilmiah mahasiswa Pendidikan biologi di Kalimantan Selatan. Hasil penelitian ini dapat menjadi pertimbangan dalam pengembangan kurikulum dan pemenuhan sarana prasaran pada Program Studi Pendidikan Biologi.